The Effect of Javanese Language Educational Video on Compliance Blood Pressure Examination in Elderly People with A History of Hypertension at Posyandu Lansia Melati 5 Kepanjen Health Center Working Area - Friska Pricilia Wibowo; Ganif Djuwadi; Atti Yudiernawati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Hypertension is the medical term for high blood pressure. Hypertension is commonly referred to as